KESIAPSIAGAAN RUMAH TANGGA DALAM MENGHADAPI BENCANA LETUSAN GUNUNG KERINCI DI LERENG SELATAN GUNUNG KERINCI - Wellasya Eka Deni; Ernawati Ernawati (JURNAL BUANA, 2020)
Abstract This study aims to determine (1) the knowledge and attitudes of households in facing the eruption of Mount Kerinci on the southern slopes of Mount Kerinci (2) emergency response plans for households facing the eruption of Mount Kerinci on the southern slopes of Mount Kerinci (3) Disaster warning systems at home stairs facing the eruption of Mount Kerinci on the southern slopes of Mount Kerinci (4) Mobilization of resources in households facing the eruption of Mount Kerinci on the southern slopes of Mount Kerinci (5) The level of household preparedness in facing the eruption of Mount Kerinci on the southern slopes of Mount Kerinci. This type of research is descriptive quantitative. With data analysis, namely the analysis of the level of preparedness according to LIPI-UNESCO, the population of this study were households in the South Slope of Mount Kerinci, this study used a sample of 5% of the total population. The techniques used in data collection are observation, interview, questionnaire and documentation. The results of this study indicate that (1) the knowledge of households on the southern slopes of Mount Kerinci already knows the status of Mount Kerinci, the dangers and impacts of the Mount Kerinci eruption (2) Emergency response plans in households that most households choose to flee to a safer place. (3) The disaster warning system uses loudspeakers in the nearest mosque or mosque, hitting electric poles as a danger signal. (4) Mobilization of resources is still a small proportion of households who have participated in disaster socialization activities. (5) The level of household preparedness on the southern slopes of Mount Kerinci is in the almost ready category.